Contabilidade criativa e o papel do auditor independente : um estudo sobre a Americanas S/A - Silva, Ana Paula Küster da (2023)
The large-scale competitiveness in the market makes companies continually seek better results and higher profits. Given this panorama, some of them use means to manipulate financial statements and demonstrate an image that does not match reality, also called creative accounting. This study aimed to analyze the role of the independent auditor in cases of use of creative accounting by organizations. To meet the proposed objective, the methodology consisted of a descriptive, qualitative research in the analysis of documents from the Americanas S/A case published through various publications in electronic media between January 2023 and May 2023. It is known that the company used creative accounting to disguise the information through the transaction of the withdrawn risk. The study also points out that the responsibility for preventing and detecting fraud is the responsibility of the company's management and not the auditor's role, which is to ensure credibility of the entity's accounting information and issue an opinion certifying that the financial statements represent the financial position of the company in all material respects.